Matrix of Contingencies - Fong, Louise Tet (Auckland University of Technology, 2019)
This practice based project explores how tacit knowledge serves the creative process of painting by providing a foundations for deciding how to act while painting. Because tacit knowledge is not brought to consciousness, it frees our perceptual processing from having to deal with the mechanics of painting so that attention can be focused on the immediacy of the changing visual conditions. I am able to depend on this base of knowledge to allow me to pay full attention to the action of painting in the present, and to notice new and emerging possibilities. I examine the interplay of tools and processes, aesthetic and material considerations, subject matter and memory as all these factors relate to tacit consideration, and as they become interpolated into the painting process, and as they fold back into an accumulating base of experience and knowledge. This interplay between what is the known, and what is emerging as yet new experience, gives me a place to start examining the question of how painting can remains energised. This project is about understanding the implications and limitations of how I make paintings, how tacit knowledge facilitates this dynamic matrix of contingencies that brings forth the surprising, the unexpected, unplanned and unknown, and about exploring ways to enhance the vitality of my painting practice.
Keywords: Tacit knowledge; Contingencies; Disruption; Aesthetics